Introduction to English Vocabulary in Children with The Singing Method at Taman Firdaus Karanganyar Kindergarten - Hartini, Tri; Slamet, Sri (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This study endeavours to enhance children’s English vocabulary acquisition through singing activities. The impetus for this research stemmed from the prevalent challenge of impediments encountered in mastering vocabulary among children, particularly in the realm of memorising multi-syllabic English words imparted by educators. Additionally, it addresses the issue of errors or inaccuracies in comprehending the intended meaning during English language learning sessions. This research adopts a classroom action methodology executed across three phases: planning, implementation, observation, and reflection. The research cohort comprises 14 participants from Group A. Data collection methodologies encompassed the compilation of field notes, interview transcripts, and photographic documentation of the activities. Employing the singing method for English language acquisition proves to be a straightforward pedagogical approach, facilitating ease of vocabulary retention among children. Through this method, children can articulate their thoughts and emotions via melodic tones and expressions. Singing activities serve as a conduit to ignite children’s enthusiasm for learning, seamlessly integrating with the foundational principles of kindergarten education. The outcomes of this study reveal a notable enhancement in children’s English vocabulary proficiency. Progression is evident across the three stages of the intervention: from an initial attainment of 39% in stage I to 78% in stage II, and culminating in a substantial improvement to 91% in stage III. Thus, it can be inferred that the singing method constitutes an efficacious means to bolster children’s English vocabulary skills.